The Effect of Employee Performance Targets and Work Discipline on Elementary School Teacher Performance in Pasuruan Regency - Salim, Shovi Andi Fariz; Suyanto; A. Faizin (The Future of Education Journal, 2026)
Teacher performance is a key factor in educational success. This study aims to analyze the effect of Employee Performance Targets (Sasaran Kinerja Pegawai / SKP) and work discipline on teacher performance at SDN Parerejo III, Pasuruan Regency. The study employed a quantitative method using an explanatory associative causal survey approach. The research population consisted of all six teachers at SDN Parerejo III, with a census sampling technique applied. Data were collected through closed-ended questionnaires using a five-point Likert scale and analyzed using simple and multiple linear regression. The results indicate that, partially, both SKP and work discipline have a positive and significant effect on teacher performance. Simultaneously, these two variables contribute 78.2% to the variation in teacher performance. The study concludes that SKP and work discipline play an important role in improving teacher performance; therefore, it is recommended to optimize the e-performance system and strengthen a culture of discipline within schools.